2012
DOI: 10.1007/s11010-012-1463-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: PI3 kinase/Akt/HIF-1α pathway is associated with hypoxia-induced epithelial–mesenchymal transition in fibroblast-like synoviocytes of rheumatoid arthritis

Abstract: Migration and invasion of fibroblast-like synoviocytes (FLSs) are critical in the pathogenesis of rheumatoid arthritis (RA). Hypoxic conditions are present in RA joints, and hypoxia has been extensively studied in angiogenesis and inflammation. However, its effect on the migration and invasion of RA-FLSs remains unknown. In this study, we observed that RA-FLSs exposed to hypoxic conditions experienced epithelial-mesenchymal transition (EMT), with increased cell migration and invasion. We demonstrated that hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…Accumulating evidences have shown that PI3K/AKT pathway activates HIF-1 α in various disease models40, 41. Moreover, studies demonstrated that MAPK/ERK1 pathway also involved in activation of HIF-1 α42-44.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences have shown that PI3K/AKT pathway activates HIF-1 α in various disease models40, 41. Moreover, studies demonstrated that MAPK/ERK1 pathway also involved in activation of HIF-1 α42-44.…”
Section: Discussionmentioning
confidence: 99%
“…Notch-1 intracellular domain (Notch-1), Janus kinase/signal transducers and activators of transcription (JAK-STAT) and phosphoinositide 3-kinase-protein kinase B (PI3K-AKT) in synovial tissue and cells [13][14][15][16]. Evidence of a key role for metabolism in the regulation of synovial inflammation has recently emerged, where proliferation and rapid activation of immune and stromal cells requires a switch in cell metabolism from a resting regulatory state to a highly metabolically active state, in order to maintain energy homeostasis [6,17].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
“…Notch-1 intracellular domain (Notch-1), Janus kinase/signal transducers and activators of transcription (JAK-STAT) and phosphoinositide 3-kinase-protein kinase B (PI3K-AKT) in synovial tissue and cells [13][14][15][16].…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
“…Conditional knockout of HIF-1α in myeloid cells in a murine model of RA significantly reduced synovial inflammation and disease progression (57). Similarly, HIF-1α played a critical role in hypoxia-induced synovial hyperplasia and inflammatory cell infiltration in murine collagen-induced arthritis (58). HIF also induces expression of inflammatory cytokines including IL-6, IL-8, TNF-α, and IL-1β in rheumatoid synovial fibroblasts (59).…”
Section: Pathological Functions Of Angptl4 In Ramentioning
confidence: 99%